Pertumbuhan Kebutuhan Sekolah Menggunakan Graph - Safitri, Andriani Arisa; Ningrum, Alvi Dwi; Utama, Muhammad Rizky; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Quality schools are schools that are able to implement 8 Standards of National Education Standards set by the Government. These standards are made so that schools are capable of conducting good and qualified teaching and learning activities in all fields of education. Until the school can achieve maximum results from the standards given. In achieving that there are things that need to be done beforehand, namely school needs analysis. From the analysis it can be seen the growth of school needs. Growth in school needs is needed as a key to achieving quality schools. This research uses graphs to illustrate every growth that occurs in a school with the criteria for increasing students. The method used for data processing uses AHP (Analytic Hierarchy Process).